The Anabolic Effect of Fenugreek: A Systematic Review with Meta-analysis - Isenmann, Eduard; Alisauskas, Pijus; Flenker, Ulrich; Schalla, Jan; Diel, Patrick (International Journal of Sports Medicine, 2023)
The use of plant steroids to improve physical health and performance is becoming increasingly popular. One of these plant steroids is diosgenin, which is mainly available in fenugreek. As a result, some studies have been conducted to improve physical health. Fenugreek extracts are also becoming increasingly popular in the context of athletic performance. Based on these assumptions, a systematic review with meta-analysis was conducted to evaluate the promoting effects of fenugreek on strength performance, body composition, and hormone concentration. Four databases were screened according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The current version of ReviewManager (RevMan) was used for the statistical evaluation. Seven studies with 449 participants (378 male, 71 female) met the inclusion criteria. A small effect of fenugreek was detected for total testosterone (standard mean difference (SMD): 0.32; 95% confidence interval (CI): 0.09 0.55), free testosterone (SMD: 0.24; 95% CI: −0.04, 0.52), lean body mass (SMD: 0.19; 95% CI: −0.10, 0.49), fat mass (SMD: −0.19; 95% CI: −0.44, 0.05), and leg press performance (SMD: 0.22; 95% CI: −0.02, 0.47), in male athletes. The meta-analysis shows that chronic application of fenugreek has performance-enhancing and anabolic effects in male athletes, but no statements can be made for female athletes.
Keywords: muscle mass; strength training; hypertrophy; performance enhancement; fenugreek; diosgenin